The impact of taxpayer awareness, tax sanctions and the level of education on taxpayer compliance - Rediva Cinta Lidya; Amalia Berliana Putri; Amri Amrulloh (Jurnal Inovasi Pajak Indonesia, 2024)
Purpose - The study exmaines the effect of taxpayer awareness, tax sanctions, and education level on taxpayer compliance.Design/methodology/approach - The study uses a quantitative approach, utilizing survey data obtained from individual taxpayers registered at a tax office. Tests of reliability and validity are carried out to confirm the soundness of the measurement tools.Findings – The study identifies taxpayer awareness and tax sanctions as significant determinants of taxpayer compliance but education level as an insignificant factor. High informality is maintained by a general fear of being caught, rather than by formal education levels which controlled the approach of the informal worker.Originality/value – This research adds to the existing literature by offering empirical evidence around factors influencing taxpayer compliance, especially in the development of tax policies where awareness campaigns and enforcement mechanisms are prioritized. These insights will allow tax authorities to design even more effective strategies aimed at inducing the tax compliance rate.Research Implications – This study provides implications for tax administrations as it emphasizes the importance of conducting strong awareness programs along with consistent enforcement of sanctions to better ensure taxpayer compliance.